A new method for the kinematic analysis of planar four-bar mechanisms. - Hernandez, Manuel V. (Philippine Engineering Journal)
A convenient method for the analysis of planar four-bar mechanisms is achieved by applying the concept of direct linkage contraints and motion parameters based on the displacements of the mechanism. Vectors are used extensively to make the derivation simpler and to make resulting analysis equations more compact. The new method also eliminates the need to determine intermediate motion parameters. Thus, only the motion parameters of interest are obtained directly and explicitly. Higher order motion parameters are also derived from the basic linkage constraints. The formulation of the method is shown and applied to the analysis of a crank rocker and a slider crank mechanism.